1992
DOI: 10.1111/j.1600-0447.1992.tb03274.x
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth of schizophrenics in Mississippi, USA

Abstract: Prior reviews indicate that schizophrenics tend to be born in the winter, relative to non-psychiatric controls. This conclusion has been criticized, however, as the association between birth seasonality and schizophrenia may be the result of a statistical artifact, the age-incidence effect. To examine this possibility, we studied the birth seasonality of 2892 schizophrenics, controlling for the age-incidence effect. Both before and after instituting these controls, we found excesses for the months of December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This evidence has accumulated in studies of second‐trimester influenza infections. Epidemiological investigations reveal that influenza infection during the second trimester of pregnancy has been repeatedly associated with schizophrenia in progeny (Mednick et al, 1988; Kendall and Kemp, 1989; Barr et al, 1990; Rodrigo et al, 1992; Adams et al, 1993; Mcgrath and Castle, 1995). A secondary body of research has also provided epidemiological evidence that second‐trimester influenza exposure may also be associated with affective disorders, including depression, bipolar disorder, and cycloid psychosis (Machon et al, 1997; Watson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This evidence has accumulated in studies of second‐trimester influenza infections. Epidemiological investigations reveal that influenza infection during the second trimester of pregnancy has been repeatedly associated with schizophrenia in progeny (Mednick et al, 1988; Kendall and Kemp, 1989; Barr et al, 1990; Rodrigo et al, 1992; Adams et al, 1993; Mcgrath and Castle, 1995). A secondary body of research has also provided epidemiological evidence that second‐trimester influenza exposure may also be associated with affective disorders, including depression, bipolar disorder, and cycloid psychosis (Machon et al, 1997; Watson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies, especially in countries of the northern hemisphere, have reported that more schizophrenics are born during winter and early spring than during other seasons (1)(2)(3)(4)(5)(6)(7)(8). These investigations suggests that some environmental influence acting in utero or in the early months of life, and varying with the season of year, contributes to the etiology of at least some forms of schizophrenia (such as viral infection, obstetric or perinatal complications, malnutrition, vitamin deficiency or temperature) (9,10).…”
mentioning
confidence: 99%
“…But while uncertainties in diagnosis might explain a negative result in this type of study, they could hardly account for the differences found [7]. Many researchers have discussed artifacts in season-of-birth results [3][4][5][8][9][10][11][12][13][14][15][16][17][18][19], and most have found evidence of a winter spring excess among schizophrenic births.…”
Section: Introductionmentioning
confidence: 99%